Incremental value of preoperative right ventricular function in predicting moderate to severe acute kidney injury after heart transplantation - Zhu, Shuangshuang; Zhang, Yanting; Qiao, Weihua; Wang, Yixuan; Xie, Yuji; Zhang, Xin; Wu, Chun; Wang, Guohua; Li, Yuman; Dong, Nianguo; Xie, Mingxing; Zhang, Li (Frontiers in Cardiovascular Medicine, 2022)
Background: Acute kidney injury (AKI) commonly occurs after heart transplantation (HTx), but its association with preoperative right ventricular (RV) function remains unknown. Consequently, we aimed to determine the predictive values of preoperative RV function for AKI severity after HTx. Methods: From January 1st, 2016 to December 31st, 2019, all consecutive HTx recipients (n = 379) in our center were enrolled and analyzed for the occurrence of postoperative AKI staged by the kidney disease improving global outcome criteria. Conventional RV function parameters, including RV fractional area change (RVFAC) and tricuspid annular plane systolic excursion (TAPSE) were obtained. Results: Postoperative AKI occurred in 209 (77%) patients, including 122 (45%) stage 1, 49 (18%) stage 2, and 38 (14%) stage 3 AKI. Patients with a higher AKI stage had a lower baseline estimated glomerular filtration rate (eGFR), more frequent diabetes, a higher right atrial pressure (RAP), longer cardiopulmonary bypass (CPB) duration, more perioperative red blood cell (RBC) transfusions, worse preoperative RV function. A multivariate logistic regression model incorporating previous diabetes mellitus (odds ratio (OR): 2.21; 95% CI: 1.06 to 4.61; P = 0.035), baseline eGFR (OR: 0.99; 95% CI: 0.97 to 0.10; P = 0.037), RAP (OR: 1.05; 95% CI: 1.00 to 1.10; P = 0.041, perioperative RBC (OR: 1.18; 95% CI: 1.08 to 1.28; P < 0.001) and TAPSE (OR: 0.84; 95% CI: 0.79 to 0.91; P < 0.001) was established to diagnose AKI stage 2 and 3 more accurately (AUC = 79.8 %; Akaike information criterion: 274). Conclusions: Preoperative RV function parameters provide additional predicting value over clinical and hemodynamic parameters, which are imperative for risk stratification in HTx patients at higher risk of AKI.